2014
DOI: 10.1590/s1808-18512014130300r80
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bone density in patients with scoliosis neuromuscular secondary to cerebral palsy

Abstract: OBJECTIVE: To evaluate bone mineral density in patients with neuromuscular scoliosis secondary to spastic quadriplegic cerebral palsy. METHODS: A prospective descriptive study in which, in addition to bone densitometry, the anthropometric data of the patients were assessed. As inclusion criterion we adopted patients with spastic quadriplegic cerebral palsy, wheelchair users, aged between 10 and 20 years and with neuromuscular scoliosis. RESULTS: We evaluated 31 patients, 20 female, whose average age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Several further studies have shown low BMD values in children with CP, with results ranging from 68% to 97% of the examined children [ 23 27 ]. In our study, based on the latest recommended diagnostic criteria [ 23 , 26 , 27 ], all of the examined children had osteopenia, i.e., reduced BMD, and 23.33% of them had osteoporosis. A percentage this high could be explained, by the families of the patients living in less-developed areas of our country, and that the majority of patients grew in poor conditions, which had a significant impact on nutrition and care of the children [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 77%
“…Several further studies have shown low BMD values in children with CP, with results ranging from 68% to 97% of the examined children [ 23 27 ]. In our study, based on the latest recommended diagnostic criteria [ 23 , 26 , 27 ], all of the examined children had osteopenia, i.e., reduced BMD, and 23.33% of them had osteoporosis. A percentage this high could be explained, by the families of the patients living in less-developed areas of our country, and that the majority of patients grew in poor conditions, which had a significant impact on nutrition and care of the children [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 77%